(untitled) (Journal of Gender and Social Issues, 2019)
This study negotiates the subversion of the hegemony of the feminine gender construction through analysis of Mohsin Hamid’s Moth Smoke by arguing that Mumtaz, the protagonist, does not come up to her culturally conferred feminine gender role since she is an untraditional character in the novel. Contextually, the dominant masculine traits of Mumtaz’ personality have been negotiated. This research analyses how Mumtaz resists patriarchal norms by adopting the opposite gender role and her performance as a male in the light of Butler’s views. Judith Butler has talked about the destabilization of the concept of fixed gender identities by emphasizing the concepts of non- fixed gender and ‘gender performativity’ in her book. The analysis presents the crux that marginalization of the women has been responded to by women in post- modern scenario through rejection of gender performativity. This research is qualitative and descriptive in design and is based on textual analysis.